2022
DOI: 10.1007/s00420-021-01829-1
|View full text |Cite
|
Sign up to set email alerts
|

Timber-colonizing gram-negative bacteria as potential causative agents of respiratory diseases in woodworkers

Abstract: Occurrence Gram-negative bacteria occur commonly in the inner tissues of stored coniferous and deciduous timber, showing a marked variation in numbers. The greatest maximal numbers are found in the sapwood of coniferous timber. The common constituents of the Gram-negative biota are potentially pathogenic species of Enterobacteriaceae family of the genera Rahnella, Pantoea, Enterobacter, and Klebsiella. The air of wood-processing facilities is polluted with the wood-borne Gram-negative bacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…organic dust toxic syndrome (ODTS) [14,15,16,17,18,19]. It has been demonstrated recently that Gram-negative (Gram-) bacteria and actinobacteria present in wood dust may cause hypersensitivity pneumonitis [20], whereas endotoxin (cell wall lipopolysaccharide) produced by Gram-bacteria may be a common cause of ODTS [21]. Belin and Land et al carried out a study at Swedish sawmills and found that the kiln drying was contributing factor to the high mould exposure in the trimming departments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…organic dust toxic syndrome (ODTS) [14,15,16,17,18,19]. It has been demonstrated recently that Gram-negative (Gram-) bacteria and actinobacteria present in wood dust may cause hypersensitivity pneumonitis [20], whereas endotoxin (cell wall lipopolysaccharide) produced by Gram-bacteria may be a common cause of ODTS [21]. Belin and Land et al carried out a study at Swedish sawmills and found that the kiln drying was contributing factor to the high mould exposure in the trimming departments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Timber-colonizing gram-negative bacteria are found in high numbers in sapwood of coniferous timber. Common bacteria include Enterobacteriaceae family of the genera of Rahnella , Pantoea , Enterobacter and Klebsiella [6]. During industrial processing endotoxin is released into wood dust as nano-sized microvesicles.…”
Section: Constituents Of Wood Dustmentioning
confidence: 99%
“…A review of occupational exposures to wood dust in the European Union suggested that workers in construction, furniture, builders' carpentry, joinery, sawmilling and forestry were the highest exposed [5]. Furthermore, high exposures have also been reported in plywood and chipboard factories, pulp and paper mills, composting, wood pellet production, and use of wood chips in biofuel or bedding for animals [2,6]. Studies on the African continent have also reported excessive dust exposures in small to large-scale wood factories and particleboard companies [1].…”
Section: Occupations and Populations At Riskmentioning
confidence: 99%
“…Some Pseudomonadota and other prokaryotes are able to obtain nutrients via mycophagy, which from the fungal viewpoint, is the negative end of interactions (Tláskal & Baldrian, 2021). Bacteria belonging to the genera Bacillus , Pseudomonas , Alcaligenes , Serratia, Streptomyces , Erwinia and Enterobacteria , among others, have been shown to play a role in the deterioration of building timber (Boutelje & Bravery, 1968; Dutkiewicz et al, 1992; Gaylarde & Morton, 1999; Line, 2003; Rogers & Baecker, 1991; Wójcik‐Fatla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%